Measurement of strain caused by residual stresses in a welded joint using neutron diffraction - Gubeljak, Nenad (Kovine zlitine tehnologije, 1999)
The distribution and amount of residual stresses can significantly contrubute to the fatigue fracture behaviour of welded joints in structures. Interior residual stresses, which interact with the plane strain state, are more dangerous than residual stresses at the surface of the welded joint. If the surface of the welded joint is mechanically treated (e.g. shapering), then significant differences between the stress stated at the surface and within the volume occur. Hence, different non-destructive methods (e.g. gamma radiation, neutron diffraction) have been developed to determine strains caused by residual stresses in the volume of polycrystalline materials. However, the measurement of strains caused by residual stresses becomes difficult for large samples. In this paper the measurement procedure on a sample taken from the weld joint is presented and the effecet of residual stresses on fatigue crack propagation is assessed for low and high cycle loading fatigue.
Keywords: neporušitvene metode; napetosti; zvarni spoji; utrujanje materiala